HUBUNGAN ANTARA INTELIGENSI, KETERAMPILAN PERSEPSI VISUAL DENGAN PRESTASI BELAJAR MATEMATIKA SISWA [CORRELATION BETWEEN STUDENTS' INTELLIGENCE, VISUAL PERCEPTION SKILLS, AND MATHEMATICS LEARNING ACHIEVEMENT] - Danny Kurniawan Tania (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2021)
Students’ mathematics achievement is the priority for the XYZ elementary school, but particularly in 2015 and 2016 school’s years, there was about 39% student who had poor mathematics achievement and didn’t pass the school’s minimum requirement. In most cases, student’s mathematics achievement is generally affected by two internal factors such as: student’s intelligence and visual perceptual skills. The aim of this research is to examine the relationship between intelligence, visual perceptual skills and the students’ mathematics achievement. The subject of this study were grade two and grade three students with the total sample of 43 pupils. This study employed the Test of Visual Perceptual Skills-third edition (TVPS-3) and the Culture-Fair Intelligence Test (CFIT). The results of this study showed that there was a positive and significant correlation between intelligence, visual perceptual skills and mathematics achievement. A correlation value of 0.664 was obtained for the relationship between intelligence and mathematics achievement. A correlation value of 0.723 was obtained for the relationship between visual perceptual skills and mathematics achievement and a correlation value of 0.903 was obtained for the relationship between intelligence and visual perceptual skills. These findings indicate that the higher the level of the student’s intelligence and visual perceptual skill, the higher their mathematics achievement too.